Desempenho de agentes de controle biológico no biocontrole e bioestimulo na cultura da soja (Glycine max (L.) Merrill) - Santos, Joeliton Campani dos (2025)
Soybean (Glycine max [L.] Merrill) is the main oilseed produced worldwide. The oil and protein extracted from its grains serve as a basis for human and animal food and raw material for the production of biofuels. Brazil occupies the position of largest producer and exporter of the commodity. However, some factors cause limitations in high yields, such as diseases, commonly managed with chemical pesticides which generate contamination of ecosystems and resistance of pathogens. Given the demand for food produced in a more sustainable way, bioinputs emerge as an alternative. In this sense, the present work aimed to evaluate the effect of isolates of B. velezensis, B. megaterium and T. longibrachiatum on the induction of resistance, solubilization of nutrients, growth promotion and biocontrol of pathogens that affect soybean crops. The experiments were carried out at the Federal Technological University of Paraná, Dois Vizinhos Campus. With the four isolates, the pathogens C. truncatum, C. kikuchii, S. glycines, S. sclerotiorum, M. phaseolina, R. solani, D. longicolla and F. tucumaniae were compared in vitro. The solubilization capacity of potassium in Pikovskara medium and phosphorus in NBRIP medium was also evaluated. In a greenhouse, the isolates were applied to soybean, and analyses of enzymes linked to the induction of resistance in plants were evaluated, which include: determination of chitinase, β 1,3 glucanase, total proteins, phenylalanine ammonialiase and phenolic compounds. The growth promotion study was conducted in pots, evaluating the root system and shoot. The adopted design was completely randomized with four replications. The data obtained were submitted to the Shapiro-Wilk normality test, ANOVA, followed by regression analysis in the Rbio software. The results indicate that the isolates present antagonistic effect of the confronted pathogens, presenting good performance as a phosphorus solubilizer, while for potassium only T. longibrachiatum stood out. And they induced the production of the enzymes chitinase and the β 1,3 glucanase. As well as growth promotion activity in soybean plants treated with the isolates.